Islamic finance in Indonesia: A quantum leap - Zul Kepli, Mohd Yazid (TransStellar, 2013)
Islamic finance is emerging as a rapidly growing part of the financial sector and it has become a global phenomenon. Both Muslim and western countries have accepted it into their financial portfolio. Indonesia’s Islamic banking assets have grown by 50% to US$17 billion in 2012, and are expected to continue on an upward trajectory as the Indonesian government and financial institutions show more support towards this growing sector. This research studies the development of Islamic finance in Indonesia. It analyzed the advantages, strength and benefit of Islamic banking in Indonesia such as huge domestic market, in addition to investments and economic opportunities. This research also highlights the challenges facing Islamic financial industry in Indonesia together with suggestions for improvement.